Intraepithelial lymphocytes in human oral diseases - Zhou, Dong-Yang; Bao, Chao-Fan; Zhou, Gang (Frontiers in Immunology, 2025)
ObjectiveAs a distinctive subset of T cells, intraepithelial lymphocytes (IELs) are found in the epithelium of mucosal barrier and serve as the primary defenders of the intestinal mucosal immune system. IELs exhibit phenotypic and functional diversity with high expression of activated marker molecules, tissue-homing integrins, NK cell receptors, cytotoxic T cell-related molecules, and cytokines. Meanwhile, IELs demonstrate differentiation plasticity, antigen recognition diversity, self-reactivity, and rapid “memory” effect, which enable them to play a crucial role in regulating responses, maintaining mucosal barriers, promoting immune tolerance, and providing resistance to infections. In addition, IELs have been explored in autoimmune diseases, inflammatory diseases, and cancers. However, the specific involvement and underlying mechanisms of IELs in oral diseases have not been systematically discussed.MethodsA systematic literature review was conducted using the PubMed/MEDLINE databases to identify and analyze relevant literatures on the roles of IELs in oral diseases.ResultsThe literature review revealed the characteristics of IELs and emphasized the potential roles of IELs in the pathogenesis of oral lichen planus, oral cancers, periodontal diseases, graft-versus-host disease, and primary Sjogren’s syndrome.ConclusionThis review mainly focuses on the involvement of IELs in oral diseases, with a particular emphasis on the main functions and underlying mechanisms by which IELs influence the pathogenesis and progression of these conditions.